Jornal brasileiro de doenças sexualmente transmissíveis : DST - Sociedade Brasileira de Doenças Sexualmente Transmissíveis (Editora Cientifíca Nacional, 1989)
Suitable and reliable instrument to spread qualified scientific knowledge in the field of DST/ STD/ Sexually Transmitted Infections (STI) / HIV-AIDS.
Keywords: Sexually transmitted diseases : Periodicals; Sexually transmitted diseases : Brazil : Periodicals; Sexually Transmitted Diseases; Brazil